Experimental study on dynamic behavior of ball bearing cage in cryogenic environments, Part I: Effects of cage guidance and pocket clearances - Choe, Bokseong; Lee, Jeonkook; Jeon, Doyoung; Lee, Yongbok (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2019)
In cryogenic environments, it is not possible to apply oil or grease to ball bearings, owing to the extreme temperature conditions. Thus, polytetrafluoroethylene (PTFE) cages are used as solid lubricants in such environments, because PTFE has a low coefficient of friction. PTFE cages increase the rotational stability of the ball bearings by reducing the frictional force of the rolling elements. In addition, design parameters such as the cage guidance and ball-pocket clearances significantly affect the stability of the ball bearings. In this study, the dynamic behavior of a ball bearing cage submerged in a cryogenic fluid was investigated for different cage clearances and rotation speeds. For experimental verification, a test rig was designed to realize a cryogenic environment. The test rig could be driven to 11,000 rpm using a DC motor and provided loads of up to 20 kN using a pneumatic cylinder. A metal ring was employed to measure the cage whirling amplitude using a fiber optic displacement sensor. The parameters considered included the cage whirling amplitude, ball bearing torque, and cage wear. The effects of the clearances and rotation speed on the cage stability and performance were analyzed using the probability density function of the cage whirling frequency, and the standard deviation of this function decreased as the outer guidance clearance decreased. In addition, the cage wear loss increased with decreasing cage ball-pocket clearance, owing to the collisions between the balls and cage pocket. The experimental results agreed partially with the existing theory and demonstrated that the cage instability increased as the cage guidance clearance increased. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: CYLINDRICAL ROLLER BEARING; ROLLING-ELEMENT BEARINGS; FRICTIONAL INSTABILITIES; DIAGNOSIS; STIFFNESS; RETAINER; MOTIONS; TORQUE; MODEL